Battery-grade iron phosphate as well as preparation method and application thereof

By mixing the waste iron sheet with the phosphoric acid solution and adding specific substances to one-step oxidation during the reaction, the cost is successfully reduced and the indicators of iron phosphate are improved, and the problems of high cost and poor index in traditional processes are solved, and the preparation of high-performance battery-grade iron phosphate is achieved.

CN119660695APending Publication Date: 2025-03-21WANHUA CHEM GRP CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411876158.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the traditional iron phosphate production process, the use of reduced iron powder leads to high costs and the produced iron phosphate index is poor, affecting the performance of subsequent lithium iron phosphate batteries.

Method used

The waste iron sheet is ground into iron powder and mixed with the phosphoric acid solution, and the reduced iron powder, ascorbic acid and chloramine-T are added to react to obtain the ferrous dihydrogen phosphate solution, and iron phosphate is obtained through one-step oxidation, followed by washing, drying and roasting to obtain battery-grade iron phosphate.

Benefits of technology

The use of costly reduced iron powder is reduced, and the iron phosphate produced has a high-iron-phosphorus ratio, a large tap density, and a certain carbon content, which improves the performance of lithium iron phosphate batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses battery-grade iron phosphate and a preparation method and application thereof.The method comprises the steps that 1, waste iron sheets are ground into iron powder to be mixed with a phosphoric acid solution, reduced iron powder, ascorbic acid and chloramine-T are added in the mixing process for a reaction, solid-liquid separation is conducted after the reaction, a ferrous dihydrogen phosphate solution is obtained, and the pH of the ferrous dihydrogen phosphate solution is 1.5-3.0; and (2) oxidizing the ferrous dihydrogen phosphate solution into iron phosphate in one step by adopting an oxidizing agent, carrying out solid-liquid separation to obtain an iron phosphate solid, washing and drying the iron phosphate solid, and roasting in an inert atmosphere environment to obtain the battery-grade iron phosphate. According to the invention, the use of high-cost reduced iron powder is reduced, and the produced iron phosphate has the characteristics of high iron-phosphorus ratio and high tap density, has certain carbon content, and has a wide prospect in the application of lithium iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery material preparation, and in particular to a battery-grade iron phosphate and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate batteries have the characteristics of good safety, high specific energy and power, and long cycle life. They are widely used in backup power supplies, large-scale energy storage, and electric vehicles. Lithium iron phosphate batteries are generally composed of positive electrodes, negative electrodes, diaphragms, electrolytes, shells, and other accessories. The positive electrode active material is olivine-type lithium iron phosphate (LiFePO4), which is often modified by carbon coating, doping, etc. before use.

[0003] Iron phosphate is a precursor for preparing lithium iron phosphate. Its own indicators such as iron-phosphorus ratio and specific surface area have a great influence on the subsequent performance of lithium iron phosphate. Traditional iron phosphate production processes include ammonium method, sodium method, iron method, etc. Among them, the ammonium method and sodium method will produce a large amount of sodium sulfate and ammonium sulfate as by-products. The traditional iron method requires the use of reduced iron powder, which is relatively expensive. Summary of the invention

[0004] In order to solve the above problems in the background technology, the main purpose of the present invention is to provide a battery-grade iron phosphate and a preparation method and application thereof, which reduces the use of costly reduced iron powder, and the produced iron phosphate has the characteristics of high iron-phosphorus ratio, high tap density, and a certain carbon content.

[0005] In order to achieve one aspect of the above purpose, the present invention adopts the following technical scheme: a method for preparing battery-grade iron phosphate, comprising the following steps:

[0006] 1) Grinding waste iron sheets into iron powder and mixing with phosphoric acid solution, adding reduced iron powder, ascorbic acid and chloramine-T during the mixing process to react, and separating the solid and liquid after the reaction to obtain a ferrous dihydrogen phosphate solution, wherein the pH of the ferrous dihydrogen phosphate solution is 1.5-3.0;

[0007] 2) Using an oxidant to oxidize the ferrous dihydrogen phosphate solution into ferric phosphate in one step, separating the solid from the liquid to obtain solid ferric phosphate, washing, drying and calcining the solid ferric phosphate in an inert atmosphere to obtain battery-grade ferric phosphate.

[0008] Furthermore, in step 1), the scrap iron is ground into fine powder of 10-100 μm, preferably 20-80 μm. The above parameter settings can reduce the particle size of the raw material and improve the reaction efficiency.

[0009] Further, in step 1), phosphoric acid is configured into a 10-50wt% phosphoric acid aqueous solution, wherein the molar ratio of phosphoric acid to waste iron powder is mixed according to a ratio of 1-5:1, preferably 1.5-4.0:1, which is the molar ratio of P to Fe herein. The above parameter settings can promote the full conversion of iron powder and improve the utilization rate of phosphoric acid.

[0010] Furthermore, in step 1), the iron powder is mixed with the phosphoric acid solution, comprising: mixing the iron powder with phosphoric acid and water at an ambient temperature of 40-90° C. for 60-300 minutes, with a stirring speed of 20-200 rpm. The preferred temperature is 60-90° C., and the preferred speed is 50-150 rpm. The above parameter settings can make the reaction more complete.

[0011] Further, in step 1), the molar ratio of reduced iron powder to waste iron powder is 0.5-3:1, preferably 1.2-2.5:1, ascorbic acid is added in a mass ratio, and the addition amount is 1-10wt% of the total iron powder mass, illustratively 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, preferably 2-8:100, and the amount of chloramine-T added depends on the pH, for example: the pH is controlled at 1.5-3.0 by the addition of chloramine-T. By adding ascorbic acid and chloramine-T, the oxidation of ferrous liquid is suppressed and its stability is improved.

[0012] In the present invention, the total iron powder includes waste iron powder and reduced iron powder.

[0013] Furthermore, in step 2), the oxidant used is one or more of hydrogen peroxide, sodium peroxide, sodium hypochlorite, and ozone.

[0014] Furthermore, in step 2), the molar ratio of the oxidant to the waste iron powder is 1-5: 1. Here, it is the molar ratio of the oxidant to Fe. Setting the above parameters can ensure the reaction effect while improving the overall economy.

[0015] Furthermore, in step 2), the oxidant is added at a uniform speed for 10-30 minutes, preferably under heating and stirring; the oxidation temperature is 20-90°C, and the oxidation time is 1-5 hours. The above parameter settings can make the oxidation more complete and improve the conversion rate of divalent iron.

[0016] Furthermore, in step 2), the iron phosphate solid is washed with deionized water and then dried at 100-150°C after washing.

[0017] Furthermore, in step 2), the calcination temperature is 300-800° C., the calcination time is 1-10 h, and the inert atmosphere is preferably nitrogen. The calcination according to the above parameters can dehydrate the dihydrated iron phosphate to obtain battery-grade iron phosphate.

[0018] A second aspect of the present invention provides a battery-grade iron phosphate prepared by the above method.

[0019] Furthermore, the battery-grade iron phosphate has an iron-to-phosphorus ratio greater than 0.98 and a tap density greater than 1.2 g / cm 3 , and has a certain carbon content, the carbon content range is 0.5-2.5wt%.

[0020] A third aspect of the present invention provides use of the battery-grade iron phosphate as described above or the battery-grade iron phosphate prepared by the above method in preparing a lithium iron phosphate precursor.

[0021] Compared with the prior art, the present invention has the following advantages: the present invention grinds waste iron sheets into iron powder and mixes the iron powder with phosphoric acid, adds reduced iron powder, ascorbic acid and chloramine-T in the mixing process to react, and obtains a ferrous dihydrogen phosphate solution; the ferrous dihydrogen phosphate solution after pH adjustment is oxidized into ferric phosphate in one step, and the obtained ferric phosphate solid is washed, dried and roasted in a nitrogen environment to obtain battery-grade ferric phosphate.

[0022] In the present invention, ascorbic acid plays a dual role. On the one hand, it cooperates with iron powder to play a reducing + anti-oxidation role. The reducibility of ascorbic acid can reduce the amount of iron powder added, and the anti-oxidation effect protects the ferrous dihydrogen phosphate solution to prevent it from deteriorating in an air environment. On the other hand, the role is carbon coating. After the iron phosphate obtained by the present invention is roasted and dehydrated in a nitrogen environment, the carbon in the ascorbic acid will remain, which is equivalent to obtaining an in-situ carbon-coated iron phosphate, and the iron lithium electric performance obtained by the iron phosphate is better. Chloramine-T can fine-tune the pH of the reaction solution and improve the antioxidant capacity of ascorbic acid.

[0023] The present invention uses waste iron sheets to prepare battery-grade iron phosphate through the above-mentioned reduction-oxidation process, wherein the iron conversion rate is greater than 98%, the iron-phosphorus ratio of the obtained iron phosphate is greater than 0.980, and the tap density is greater than 1.2g / cm 3 , and has a certain carbon content, the resulting lithium iron phosphate 1C reaches 150mAh / g.

[0024] Other features and advantages of the present invention will be described in detail through the following detailed description. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are shown in the examples, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.

[0026] The raw material information is as shown in Table 1:

[0027] Table 1

[0028] raw material factory Specification Reduced iron powder Beijing Inotech Technology Co., Ltd. 99.995% Phosphoric acid Beijing Inotech Technology Co., Ltd. 85% Ascorbic acid (vitamin C) Beijing Inotech Technology Co., Ltd. 95% Chloramine-T Beijing Inotech Technology Co., Ltd. 98% Hydrogen Peroxide Beijing Inotech Technology Co., Ltd. 30% Sodium hypochlorite Beijing Inotech Technology Co., Ltd. 99%

[0029] In the embodiment of the present invention:

[0030] Iron residue was analyzed by Perkin Elmer OPTIMA 2000DV ICP instrument;

[0031] The tap density was tested using Dandong Better BT-1001 intelligent powder property tester;

[0032] The iron-phosphorus ratio is tested using the protocol described in industry standard HG / T 4701-2021;

[0033] The power-on performance is tested using the scheme described in the national standard GB / T 42161-2022.

[0034] Example 1

[0035] Take the scrap iron sheet, crush it with a double-roll crusher, grind it into fine powder with a Raymond mill, and obtain a fine powder with a D50 of about 30μm after airflow classification. Take 206g of the fine powder, 350g of 85wt% phosphoric acid, and 755g of water, and stir for 30min at 80℃ and 130rpm. After stirring, add 100g of reduced iron powder and 30g of vitamin C, add chloramine-T, and adjust the pH to 2.8. Continue stirring for 120min and filter to obtain a ferrous dihydrogen phosphate solution. Then, stir the ferrous solution at 80℃, the speed is 130rpm, add 940g of hydrogen peroxide within 20 minutes, continue to react for 120 minutes, filter, wash, and dry at 120℃ to obtain dihydrate ferric phosphate. Then roast for 4h under a nitrogen environment at 580℃ to obtain battery-grade iron phosphate. The obtained iron phosphate has an iron-phosphorus ratio of 0.985 and a tap density of 1.23g / cm 3 The carbon content is 0.53wt%, and the iron lithium 1C discharge capacity is 152mAh / g.

[0036] Example 2

[0037] The difference from Example 1 is that: the addition amount of vitamin C and chloramine-T is controlled, the specific addition amount of vitamin C is 45g, chloramine-T is added, and the pH is adjusted to 2.0; the obtained product performance is as follows:

[0038] The carbon content is 1.95wt%, and the iron-phosphorus ratio of the obtained iron phosphate is 0.988 as measured by titration, and the tap density is 1.35g / cm 3 The 1C discharge capacity of lithium iron is 155mAh / g.

[0039] Example 3

[0040] The difference from Example 1 is that chloramine-T is added to adjust the pH of ferrous dihydrogen phosphate to 1.6, and the obtained product performance is as follows:

[0041] The iron-phosphorus ratio of the obtained iron phosphate was 0.991 by titration, and the tap density was 1.22 g / cm 3 , carbon content is 0.61wt%, and the iron lithium 1C discharge capacity is 153mAh / g.

[0042] Example 4

[0043] The difference from Example 1 is that the amount of vitamin C added is 2.0 g; the properties of the obtained product are as follows:

[0044] The carbon content is 0.03wt%, and the iron-phosphorus ratio of the obtained iron phosphate is 0.982 by titration, and the tap density is 1.13g / cm 3 The 1C discharge capacity of lithium iron is 149mAh / g.

[0045] Comparative Example 1

[0046] Take scrap iron sheets, crush them with a double-roll crusher, grind them into fine powder with a Raymond mill, and obtain fine powder with a D50 of about 30μm after airflow classification. Take 206g of the fine powder, 350g of 85wt% phosphoric acid, and 755g of water, and stir them at 80℃ and 130rpm for 30min. After stirring, add 100g of reduced iron powder. Continue stirring for 120min and filter to obtain ferrous liquid. Then, stir the ferrous liquid at 80℃, add 940g of hydrogen peroxide within 20 minutes, continue to react for 120 minutes, filter, and wash to obtain dihydrate ferric phosphate. Then roast at 580℃ in a nitrogen environment for 4h to obtain battery-grade iron phosphate. The iron-phosphorus ratio of the obtained iron phosphate was measured by titration to be 0.943, and the tap density was 0.82g / cm 3 The 1C discharge capacity of lithium iron is 132mAh / g.

[0047] The difference between Comparative Example 1 and Example 1 is that ascorbic acid and chloramine-T are not added in Comparative Example 1. Comparison between the two shows that the iron-phosphorus ratio of the ferrous phosphate obtained in this scheme is relatively low, indicating that the ferrous solution deteriorates during the preparation process and the utilization rate of iron is insufficient, thereby reducing the iron-phosphorus ratio of the product.

[0048] Comparative Example 2

[0049] The difference from Example 1 is that chloramine-T is not added, and ammonia water is used to adjust the pH to 2.8. The obtained product performance is as follows: the iron-phosphorus ratio of the obtained ferric phosphate is 0.948 as measured by titration, and the tap density is 0.942 g / cm 3 The carbon content is 0.24wt%, and the iron lithium 1C discharge capacity is 126mAh / g.

[0050] Comparison between Comparative Example 2 and Example 1 shows that the addition of chloramine-T can synergize with ascorbic acid to improve its reducing ability, thereby improving the utilization rate of iron and maintaining its iron-phosphorus ratio at a higher level.

[0051] Comparative Example 3

[0052] Take the scrap iron sheet, crush it with a double-roll crusher, grind it into fine powder with a Raymond mill, and obtain a fine powder with a D50 of about 230μm after airflow classification. Take 206g of the fine powder, 350g of 85wt% phosphoric acid, and 755g of water, and stir for 30min at 80℃ and 130rpm. After stirring, add 100g of reduced iron powder and 30g of vitamin C, add chloramine-T, and adjust the pH to 4.0. Continue stirring for 120min and filter to obtain a ferrous dihydrogen phosphate solution. Then, stir the ferrous solution at 80℃, add 940g of hydrogen peroxide within 20 minutes, continue to react for 120 minutes, filter, and wash to obtain dihydrate ferrous phosphate. Then roast for 4h under a nitrogen environment at 580℃ to obtain battery-grade iron phosphate. The obtained iron phosphate was measured by titration to have an iron-phosphorus ratio of 0.985 and a tap density of 1.22g / cm 3 The carbon content is 0.03wt%, and the iron lithium 1C discharge capacity is 136mAh / g.

[0053] Comparison between Comparative Example 3 and Example 1 shows that if the pH is too high, it will affect the crystallization of iron phosphate, thereby reducing its 1C discharge capacity.

[0054] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing battery-grade iron phosphate, characterized in that: The steps include: 1) Grinding waste iron sheets into iron powder and mixing with phosphoric acid solution, adding reduced iron powder, ascorbic acid and chloramine-T during the mixing process to react, and separating the solid and liquid after the reaction to obtain a ferrous dihydrogen phosphate solution, wherein the pH of the ferrous dihydrogen phosphate solution is 1.5-3.0; 2) Using an oxidant to oxidize the ferrous dihydrogen phosphate solution into ferric phosphate in one step, separating the solid from the liquid to obtain solid ferric phosphate, washing, drying and calcining the solid ferric phosphate in an inert atmosphere to obtain battery-grade ferric phosphate.

2. The method for preparing ferric phosphate according to claim 1, characterized in that: In step 1), the scrap iron is ground into fine powder of 10-100 μm, preferably 20-80 μm.

3. The method for preparing ferric phosphate according to claim 1 or 2, characterized in that: In step 1), the iron powder is mixed with the phosphoric acid solution, comprising: mixing the iron powder with phosphoric acid and water at an ambient temperature of 40-90° C. for 60-300 min, with a stirring speed of 20-200 rpm; preferably, the temperature is 60-90° C., and the preferred speed is 50-150 rpm.

4. The method for preparing ferric phosphate according to any one of claims 1 to 3, characterized in that: In step 1), phosphoric acid is configured into a 10-50wt% phosphoric acid aqueous solution, wherein the molar ratio of phosphoric acid to waste iron powder is 1-5:1, preferably 1.5-4.0:1; the molar ratio of reduced iron powder to waste iron powder is 0.5-3:1, preferably 1.2-2.5:1; ascorbic acid is added in a mass ratio, the amount added is 1-10wt% of the total iron powder mass, preferably 2-8:100; the amount of chloramine-T added depends on the pH, and the pH is controlled at 1.5-3.0 by the addition of chloramine-T.

5. The method for preparing ferric phosphate according to any one of claims 1 to 4, characterized in that: In step 2), the oxidant used is one or more of hydrogen peroxide, sodium peroxide, sodium hypochlorite, and ozone; Preferably, the molar ratio of the oxidant to the scrap iron powder is 1-5:

1.

6. The method for preparing ferric phosphate according to claim 1 or 5, characterized in that: In step 2), the oxidant is added at a uniform speed for 10-30 min; Preferably, the oxidation temperature is 20-90° C. and the oxidation time is 1-5 h.

7. The method for preparing ferric phosphate according to any one of claims 1 to 6, characterized in that: In step 2), the iron phosphate solid is washed with deionized water and then dried at 100-150° C. after washing; In step 2), the calcination temperature is 300-800° C., the calcination time is 1-10 h, and the inert atmosphere is preferably nitrogen.

8. Battery-grade iron phosphate prepared by the method according to any one of claims 1 to 7.

9. The battery-grade iron phosphate according to claim 8, wherein the iron-phosphorus ratio of the battery-grade iron phosphate is greater than 0.98 and the tap density is greater than 1.2 g / cm 3 , and has a carbon content of 0.5-2.5wt%.

10. Use of the battery-grade iron phosphate according to any one of claims 8 to 9 or the battery-grade iron phosphate prepared by the method according to any one of claims 1 to 7 in the preparation of a lithium iron phosphate precursor.

Citation Information

Cited By

  • Method for treating iron-containing waste residue by using waste to treat waste and battery-grade iron phosphate

    CN120841470A

  • A method for treating iron-containing waste residue by waste and battery-grade iron phosphate

    CN120841470B

  • Synthesis method of iron phosphate and iron phosphate

    CN121573659A

  • Filtering method for iron-process iron phosphate iron dissolving liquid

    CN122424642A